(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This study assessed the mineral and sensory properties of ‘àmàlà’ produced from yam (Dioscorea rotundata) and cassava (Manihot esculenta) flours flavoured with ginger (Zingiber officinale) flour. The three raw materials were individually processed into flour and mixture design generated by the design expert software version 12 was used to formulate a total of 13 runs. The results were compared with two controls; sample 1 (100% yam flour) and sample 2 (100% cassava flour). The samples were evaluated for mineral and sensory properties using standard operating procedures. The results obtained for the mineral analysis showed that the calcium, magnesium, zinc and iron contents ranged from 3.17-93.81 mg/100 g, 3.35-103.77 mg/100 g, 0.61-1.83 mg/100 g and 0.17-10.87 mg/100 g respectively. Sample 13 (55 yam flour: 30 cassava flour: 15 ginger flour) had the highest iron content. Major striking observation revealed that the addition of cassava flour to these flour samples improved the mineral content of these samples as the control, sample 1 (100% yam flour) had very little mineral content when compared to the rest of the samples. For the sensory evaluation of the ‘àmàlà’, sample 10 (50 yam flour: 30 cassava flour: 20 ginger flour) and sample 1 were the most preferred in terms of general acceptability amongst other samples on the 9-point Hedonic scale and of all the minerals analyzed in this work, only the iron content met the requirements for Recommended Dietary Allowance of iron for men and postmenopausal women.